The Perception of English Study Program Students on the Use of Project-Based Learning in Scientific Writing - Husna, Usrotul; Afrianto, Afrianto; Purwanti, Indah Tri (Universitas Ahmad Dahlan, 2024)
This research explores students' perceptions of the use of Project-Based Learning (PjBL) in the Scientific Writing Class at the English Study Program of FKIP UNRI. Employing a descriptive quantitative method, this study involved 37 students who had experienced PjBL during the class. Data were collected through a questionnaire containing 35 items across eight indicators. The results show that students have a high level of perception of Project-Based Learning (PjBL) in the Scientific Writing class, with an average score of 3.96. All indicators including relevance, clarity of objectives, application, and satisfaction-fall within the 'high' category. Overall, the findings demonstrate that the implementation of PjBL in the Scientific Writing class was positively perceived across various dimensions, including its application in learning activities, lecturer's support, student motivation, and writing skill development. There results underscore that when implemented thoughtfully, PjBL can enhance both the cognitive and affective aspects of students' learning experiences.